Integrating nature-based solutions and the conservation of urban built heritage: Challenges, opportunities, and prospects - Coombes, M; Viles, H (Elsevier, 2021)
Nature-based solutions (NbS) offer opportunities to incorporate green elements into cultural heritage conservation and management practice in cities and unlock associated co-benefits. However, concern about potential negative impacts of nature on built heritage (i.e., biodeterioration of heritage materials, loss of heritage values, and complicating practical heritage conservation and management) can act as a barrier to the uptake of NbS in some locations. We propose that NbS could be adapted, developed, and applied to address specific heritage conservation challenges as well as contribute to wider social benefits. In turn, urban built heritage can provide a valuable and largely underexplored space for NbS activities. Focussing on ten key benefits of NbS in cities (improving health, sequestering carbon, enhancing biodiversity, providing acoustic comfort, reducing the urban heat island, enhancing sustainable water management, facilitating urban agriculture, improving air quality, contributing to economic vitality through jobs and investment, and enhancing social cohesion), we illustrate how built heritage can both benefit from NbS and contribute to their wider success. We show how built heritage can benefit through reducing or mitigating the deterioration of heritage materials, improving the visitor experience, enhancing values, and stimulating investment. At the same time, built heritage conservation can support the delivery and success of NbS in cities by offering additional locations to implement and connect NbS schemes, providing inspiration for closer relationships between nature and society, and enriching NbS benefits by adding a cultural element. We conclude that flexibility is needed to link built heritage and NbS, yet the opportunities are great. Cultural and natural heritage are vital components of resilient and sustainable urban communities, fostering shared values by connecting people with the past and with nature. Better integrating built heritage into the wider NbS paradigm shows great promise for strengthening and broadening these linkages.